Validasi Metode Analisis Residu Mometasone furoate dan CIP100 Setelah Proses Pembersihan Peralatan Produksi di Industri Farmasi “XYZ” - Amaandika Galih Arintowibowo; Ririn Sumiyani; Kusuma Hendrajaya (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
In this study, the HPLC and Total Organic Carbon (TOC) analysis methods have been developed and validated for the determination of the amount of Mometasone furoate and CIP100 residues on the surface of production equipment and to confirm the efficiency of the cleaning procedure. Mometasone furoate and CIP100 have been chosen based on the worst case assessment approach. The limit of mometasone furoate contamination that has been determined is 100 ug/swab and the specified limit of CIP100 contamination is 100 ug/swab which should not be exceeded during sequential cleaning of the equipment. Mometasone furoate shows good linearity in the range 0.1-1.0 ppm for the HPLC method and CIP100 2.0-10.0 ppm for TOC Analysis. The percentage of recovery from stainless steel plates using swab sampling techniques was found in the limits of 95.12% and 99.93% respectively in the HPLC and TOC methods. Both methods are simple, inexpensive, short analysis time and high sensitivity for quantitative determination of Mometasone furoate and CIP100 on the surface of manufacturing equipment well below the contamination limit. The validated method meets the requirements for demonstration of the validation of residual cleaning of mometasone furoate and CIP100 on the surface of production equipment